2023
DOI: 10.1371/journal.pbio.3002336
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the regulatory circuit governing corneal epithelial fate determination and disease

Jos G. A. Smits,
Dulce Lima Cunha,
Maryam Amini
et al.

Abstract: The transparent corneal epithelium in the eye is maintained through the homeostasis regulated by limbal stem cells (LSCs), while the nontransparent epidermis relies on epidermal keratinocytes for renewal. Despite their cellular similarities, the precise cell fates of these two types of epithelial stem cells, which give rise to functionally distinct epithelia, remain unknown. We performed a multi-omics analysis of human LSCs from the cornea and keratinocytes from the epidermis and characterized their molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 122 publications
1
9
0
Order By: Relevance
“…IRF7 is a member of the interferon regulatory factors (IRFS) family and participates in type-I interference (IFN) signaling, and plays a role in antigen presentation function of human corneal endothelial cells [ 62 , 63 ]. The latest research showed that FOSL1 as the human LSC-specific TFs that determined the LSC fate and was important in epidermal cells [ 64 ]. Furthermore, KLF7 promoted the corneal progenitor cell state [ 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…IRF7 is a member of the interferon regulatory factors (IRFS) family and participates in type-I interference (IFN) signaling, and plays a role in antigen presentation function of human corneal endothelial cells [ 62 , 63 ]. The latest research showed that FOSL1 as the human LSC-specific TFs that determined the LSC fate and was important in epidermal cells [ 64 ]. Furthermore, KLF7 promoted the corneal progenitor cell state [ 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…To further assess the molecular profile of the FACS-purified cells, we collected samples from TRA-1-81 - /ITGA6 + /AREG + hESC and hiPSC1 at 15 days post-sorting and carried out bulk RNA-seq. The expression of selected cluster marker genes in the bulk RNA-seq data of FACS-purified cells were compared to the pseudobulk datasets from our “all D24 cells” and the primary LSCs from Smits et al 2023 (Figure 6C). Similar to the in silico purification and supporting the IF staining results, expression of genes in FACS-purified TRA-1-81 - /ITGA6 + /AREG + hiPSC1 cells showed more similarity to hESC “all D24 cells” and primary LSCs, as compared to all unpurified hiPSC1 “all D24 cells”, including increased expression of LSC markers and decreased expression of mesodermal-like and pluripotent markers.…”
Section: Resultsmentioning
confidence: 99%
“…This may require further attention in our upcoming studies, since correct dosage of PAX6 is known to be essential for corneal epithelial health, starting early on from the eye field development all the way to corneal morphogenesis and postnatal CE (Shaham et al, 2012; Sunny et al, 2022). Importantly, it is one of the key transcription factors driving the lineage-commitment toward the ocular epithelia instead of skin epidermis (Kitazawa et al, 2017; G. Li et al, 2015; Ouyang et al, 2014; Smits et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations